Prevalence of sonographic signs in women with uterine sarcoma: a systematic review and meta-analysis - Raffone, Antonio; Raimondo, Diego; Neola, Daniele; Travaglino, Antonio; Doglioli, Marisol; Ambrosio, Marco; Raimondo, Ivano; De Meis, Lucia; Turco, Luigi Carlo; Cosentino, Francesco; Seracchioli, Renato; Casadio, Paolo; Mollo, Antonio (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Objective To assess the prevalence of sonographic signs in women with uterine sarcoma.Materials and Methods A systematic review and meta-analysis were performed. Five electronic databases were searched from inception to June 2022 for all studies allowing calculation of the prevalence of sonographic signs in women with uterine sarcoma. Pooled prevalence with 95% confidence intervals was calculated for each sonographic sign and was a priori defined as “very high” when it was ≥ 80%, “high” when it ranged from 80% to 70%, and less relevant when it was ≤ 70%.Results 6 studies with 317 sarcoma patients were included. The pooled prevalence was:Conclusion Solid component, irregular walls of cystic areas, and singular lesions are signs with very high prevalence, while inhomogeneous echogenicity of solid component, anechoic cystic areas, and absence of calcifications are signs with high prevalence. The remaining signs were less relevant.
Keywords: malignancy; myomata; leiomyosarcoma; prediction; preoperative assessment